Contextualising Legal Research : a Methodological Guide - Taekema, Sanne, 1970-; van der Burg, Wibren (Cheltenham, UK : Edward Elgar Publishing, 2024)
"Providing a clear and concise guide to the practicalities of legal research, this informative book presents a methodological framework for law-in-context research design. It argues that legal scholarship relies on the interpretive and argumentative methods of the humanities, but also requires empirical input due to its focus on social reality. Contextualising Legal Research discusses core topics including research questions, methods, theoretical frameworks, evaluations and recommendations. It demonstrates how the contextualisation of doctrinal research is a gradual process: while sometimes researchers may include only the output of other disciplines, their research questions often require them to undertake more interdisciplinary research themselves. Ultimately, the book advocates a combination of doctrinal research, empirical disciplines and theoretical-normative perspectives, with extensive discussion on the contribution of the humanities to legal research. Promoting a practical examination of interdisciplinary doctrinal research, this book is an essential resource for master students and PhD candidates on research methods in law. It is also beneficial for researchers conducting doctrinal and interdisciplinary research"--
Includes bibliographical references and index.
Keywords: Legal research -- Methodology